Star crossed : a true Romeo and Juliet story in Hitler's Paris - Macadam, Heather Dune; Worrall, Simon (Citadel Press, Kensington Publishing Corp., 2023)
"Paris, 1940. The City of Light has fallen under German occupation. Among patriotic Parisians, the pursuit of art, culture, and jazz has become a bold act of defiance. So has forbidden love for talented and spirited Jewish teenager Annette Zelman, a student at the Beaux-Arts, and dashing young Catholic poet Jean Jausion. Despite their devout families' vehement opposition, the young couple finds acceptance at the famed Café de Flore, whose habitues include Simone de Beauvoir, Jean-Paul Sartre, Pablo Picasso, Django Reinhardt, and other luminaries of the Latin Quarter. For a time, Annette and Jean feel they have eluded the brute might of the relentless Nazis--and more immediately, their parents' threats and demands. But as restrictions on the Jewish community escalate to arrests and deportations, the maleficent forces gathering around the young lovers set them on divergent and tragically inevitable paths. Drawn from never-before-published family letters and other treasures, as well as archival sources and exclusive interviews, Star-Crossed offers us precious insight into the Holocaust and the lives French people bravely led under the Hitler regime. This breathtaking true story of beauty, art, liberation, and the transformative power of love resonates with an intimate story of undying devotion, seen through the prism of history"--